PENGARUH PENILAIAN KETERAMPILAN MATA PELAJARAN PPKn DALAM KURIKULUM 2013 TERHADAP PEMBINAAN TANGGUNGJAWAB WARGA NEGARA (CIVIC RESPONSIBILITY) DI SMK NEGERI SE-KOTA BANDUNG - Cahyono Cahyono; Aim Abdul Karim (Jurnal Ilmiah Mimbar Demokrasi, 2015)
Skill assessment, which is called performance assessment, is part of assessment domains in curriculum 2013. In PPKn subject, skills assessment can assistlearners to foster their attitude of solidarity, democratic, and responsible through practice assignment, project, and portfolio technique. The purpose of this research is to know how the effect of the implementation of skills assessment based on curriculum 2013 in PPKn subject toward the educationof civic responsibility on the learners. The basic theory is permendikbud No. 104 (2014) about the assessment standards and assessment theory Widoyoko (2014), the theory of civic responsibility Branson (1999). The approach used is quantitative research with survey method. A population is of 2380 students. Technique used is random sampling as many as 336 respondents. Data collection used is questionnaire, using correlation and regression analysis. Based on data analysis, influence planning (X1) and implementation skills assessment (X2) on the education of civic responsibility (Y) has positive effect amounting to 21,47%.